Cyfres Mellt - Williams, Gareth F. (Y Lolfa, 2017)
An exciting story by master novelist Gareth F. Williams for Year 7-9 pupils, with many hair-raising occurrences to keep readers looking over their shoulder time and time again. Intro – Pennod 1 – Pennod 2 – Pennod 3 – Pennod 4 – Pennod 5 – Pennod 6 – Pennod 7 – Pennod 8 – Pennod 9 – Pennod 10 – Pennod 11 – Pennod 12 – Epilog.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books